Chemoselective synthesis of beta-amino acid derivatives by hydroamination of activated olefins using AISBA-15 catalyst prepared by post-synthetic treatment - Shanbhag, Ganapati V.; Kumbar, S. M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
beta-Amino acid derivatives have a wide variety of applications viz. in the synthesis of peptide analogues, precursor for amino alcohols, optically active amino acids, lactums and diamines. Chemoselective anti-Markovnikov hydroamination reaction of activated olefins was effectively used to synthesize beta-amino acid derivatives using AlSBA-15 and AlMCM-41 catalysts. These catalysts with different Si/Al ratios were synthesized by isomorphous substitution of aluminium into the framework of SBA-15, which induces the Bronsted and Lewis acid sites. The structural integrity of the catalysts was established by characterizing with XRD, N-2-sorption, TEM, NH3-TPD Al-27 MAS NMR and Si-29 MAS NMR techniques. Hydroamination of ethyl acrylate with aniline was used as a test reaction, which gave N-[2-(ethoxycarbonyl)ethyl] aniline with high selectivity. The performance of AlSBA-15 catalyst was also determined with different acrylates and amines to know the general applicability of the catalyst in hydroamination reactions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acrylate; activated olefin; addition; AlMCM-41; AlSBA-15; Amine; beta-amino acid; Catalyst; hydroamination; Mesoporous